Modeling and simulation in distributed parameters for a dryer of cocoa beans - Rosero, P. Parra (2015 CHILEAN Conference on Electrical, Electronics Engineering, Information and Communication Technologies (CHILECON), 2015)
This paper presents a model in distributed parameters for a drying plant of cocoa beans. The plant is composed of a combustion chamber, an air fan thrust and a drying chamber integrated by a rotating cylinder. The model was developed in the EcosimPro® platform, in wich the process of simulation, sensitivity analysis and estimation of parameters were implemented. For the optimization and validation of the model were used real plant data. This research examines a valid alternative to artificial drying of cocoa beans.